2021
DOI: 10.1186/s40795-021-00410-w
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional perspectives on sickle cell disease in Africa: a systematic review

Abstract: Background Sickle cell disease (SCD) is an inherited blood disorder that predominantly affects individuals in sub-Saharan Africa. However, research that elucidates links between SCD pathophysiology and nutritional status in African patients is lacking. This systematic review aimed to assess the landscape of studies in sub-Saharan Africa that focused on nutritional aspects of SCD, and highlights gaps in knowledge that could inform priority-setting for future research. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 92 publications
0
25
0
4
Order By: Relevance
“…With regards to VOC, our meta-analysis found a neutral effect size between SCD children and controls, the wide heterogeneity decreasing after removal of the studies from India [ 29 ] and from Nigeria [ 23 , 24 , 53 ], implying that these latter contributed to the heterogeneity, possibly via the same nutritional and vitamin deficiencies alluded to earlier [ 62 ]. It should be noted that in the VOC comparison, SCD patients were unmatched, preventing the capture of the same genetic, oxidative, and nutritional background of the participants before and after crisis, that might have allowed a better interpretation of the results.…”
Section: Discussionmentioning
confidence: 68%
“…With regards to VOC, our meta-analysis found a neutral effect size between SCD children and controls, the wide heterogeneity decreasing after removal of the studies from India [ 29 ] and from Nigeria [ 23 , 24 , 53 ], implying that these latter contributed to the heterogeneity, possibly via the same nutritional and vitamin deficiencies alluded to earlier [ 62 ]. It should be noted that in the VOC comparison, SCD patients were unmatched, preventing the capture of the same genetic, oxidative, and nutritional background of the participants before and after crisis, that might have allowed a better interpretation of the results.…”
Section: Discussionmentioning
confidence: 68%
“…Stunting, wasting, being underweight, and micronutrient deficiencies are the four main ways in which undernutrition presents itself [ 11 ]. In Cameroon, few studies have been conducted on the growth and nutritional status of children with SCD [ 12 , 13 ]. Ngo Um Sap et al found a prevalence of underweight of 4% in children with SCD under 5 years of age [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sickle cell anemia (SCA), the most prevalent hereditary hemoglobinopathy in the world, with an autosomal recessive character, resulting from a mutation in the β-globin gene, characterized by homozygosity for the βS allele (Nartey et al, 2021;Sunnd et al, 2019;Piccin et al, 2019). In the SCA, the most severe form of sickle cell disease (SCD), the erythrocytes acquire a sickle shape, a cellular expression of the polymerization of deoxygenated hemoglobin S (HbS), a process that leads to hemolysis and adhesion of erythrocytes to the vascular endothelium, which results in obstruction, chronic inflammation and recurrent episodes of blood vessel occlusion (Piccin et al, 2019;Salinas Cisneros & Thein, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…SCA is a multisystemic pathology, that has high morbidity and mortality rates and is a severe public health problem (Abdul-Hussein et al, 2021;Nartey et al, 2021). It predominantly affects people of African, Indian and Arabic descent, with most cases occurring in Sub-Saharan Africa (Nartey et al, 2021;Inusa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation